2016
DOI: 10.5585/geas.v5i1.223
|View full text |Cite
|
Sign up to set email alerts
|

Processo de Mudança para uma Orientação Sustentável: Análise das Capacidades Adaptativas de Três Empresas Construtoras de Santa Maria-RS

Abstract: A raiz do pensamento em torno da sustentabilidade reside em tentar mudar a mentalidade das pessoas para uma concepção diferente de vida. Nesse propósito, as empresas desempenham um importante papel. Porém, a orientação sustentável que está baseada em uma proposta ampla ainda está sendo incipientemente implantada nas empresas. O setor de construção civil, devido a um histórico perverso no tocante aos impactos no meio ambiente e à periculosidade de suas atividades aos trabalhadores, tem sido muito visado pelo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
4
0
3
Order By: Relevance
“…Os resultados demonstram que, com base no enfoque de cada revista, o gerenciamento de resíduos é atrelado, em sua maioria, à gestão ambiental e à sustentabilidade. A relação dos estudos com a temática envolta à sustentabilidade ocorre principalmente devido aos impactos nocivos, diretos ou indiretos, que o manejo inadequado dos resíduos de construção civil causa ao meio ambiente (Yeheyis et al 2013;Brasileiro & Matos, 2015;Macêdo & Martins, 2015;Teixeira et al, 2016).…”
Section: Análise E Discussão Dos Resultadosunclassified
See 2 more Smart Citations
“…Os resultados demonstram que, com base no enfoque de cada revista, o gerenciamento de resíduos é atrelado, em sua maioria, à gestão ambiental e à sustentabilidade. A relação dos estudos com a temática envolta à sustentabilidade ocorre principalmente devido aos impactos nocivos, diretos ou indiretos, que o manejo inadequado dos resíduos de construção civil causa ao meio ambiente (Yeheyis et al 2013;Brasileiro & Matos, 2015;Macêdo & Martins, 2015;Teixeira et al, 2016).…”
Section: Análise E Discussão Dos Resultadosunclassified
“…Em relação aos temas abordados nos estudos, todos possuíam foco em gestão ambiental e sustentabilidade. Isto se dá devido a intensificação das pesquisas voltadas aos impactos nocivos das atividades produtivas ao meio ambiente, onde grupos de interesse cobram das empresas uma postura condizente com a preservação dos recursos ambientais (Yeheyis, Hewage, Alam, Eskicioglu & Sadiq, 2013;Macêdo & Martins, 2015;Teixeira et al, 2016).…”
Section: Impactos Da Atividadeunclassified
See 1 more Smart Citation
“…Cattelan, Noro and Magalhães (2012) analyzed the decision-making criteria of a PBQP-h certified building company in Santa Maria and identified a greater focus on reducing costs, as social and environmental strategies were being developed for future application. To investigate how three construction companies in Santa Maria were promoting a shift to more sustainable practices, Teixeira et al (2016) interviewed the company directors. Results indicated that tacit strategies adopted by two companies were more related to the directors' previous knowledge, and that there was no effort to share and improve collective knowledge with the team.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Nevertheless, it was observed that the construction sector in the region does not face major obstacles in adopting practices considered to be more sustainable. Teixeira, Zamberlam, Santos and Gomes (2016) investigated how three construction companies in Santa Maria -RS are transitioning into a more sustainable management, based on interviews with the directors. Some of companies' initiatives were verified, which basically varied according to their environmental policies, the importance given by senior management, and the real involvement of employees.…”
Section: Recent Researches Have Verified How Companies In the Construmentioning
confidence: 99%